Growing Older Urbanism: exploring the nexus between ageing, the built environment, and urban ecosystems - O'Neill, Desmond; Grey, Thomas; Xidous, Dimitra; Collier, Marcus (My University, 2023)
Background: Some of the main urban issues we currently face include ageing popu- lations, the impact of the built environment, and the treatment of urban ecosystems. Yet the dynamic relationships and synergies between these issues, and how they are influenced by urban growth and evolution, receives little attention. Research focus: We explore the nexus between people, the urban built environ- ment, and ecosystems as they grow, age, change, and evolve and propose an inte- grated approach to examine the relationships, synergies, and challenges that may emerge over time within urban neighbourhoods. We argue that this should draw on the lived-experience and wisdom of older people as part of an intergenerational approach underpinned by local, traditional, and ecological knowledge. We propose Growing Older Urbanism as an ecological, co-evolutionary, and complex-adaptive- systems-based framework to explore the nexus between ageing, the built environ- ment, and urban ecosystems and to reveal the synergies and antagonisms that might exist between these three elements. This framework is designed to be used for various types of urban neighbourhoods, and by a diverse range of stakeholders. As part of this approach we provide a preliminary visual canvas to illustrate how the framework might be used within a selected neighbourhood over an agreed timespan. Conclusion: This paper presents some early thinking around the Growing Older Urbanism concept, while also outlining questions and a proposed transdisciplinary research programme to further develop the framework. We argue that understanding the relationship between ageing and the co-evolution of people, place, and ecosys- tems may teach us about our past, present, and future, and help us grow towards inclusive and sustainable communities.
Keywords: Urban systems, Social-ecological systems, Age-inclusive design, Sustainability, Climate change, Co-creation, Resilience; Ageing; Identities in Transformation; Making Ireland; Nanoscience & Materials; Smart & Sustainable Planet; AGEING; Architecture and Urbanism; Architecture, Design; Biodiversity; CLIMATE CHANGE; DESIGN; E3; NATURE-BASED SOLUTIONS; Urban Geography; Urban Studies; co-creation; Age-related disability; Community; Environment and housing; Gender; Health; Home and community living; Policy; Third age/ageing